Cost accounting : a managerial emphasis. - Horngren, Charles T. (Englewood Cliffs, N.J. : Prentice-Hall, 1997)
These five tapes coincide with chapters in the 9th ed. of Cost accounting : a managerial emphasis by Charles T. Horngren, George Foster, and Srikant M. Datar.
Includes indexes.
Tapes 1 and 2 are ABC News/Prentice-Hall productions. Tapes 3 and 4 are titled: Plant tours. Tape 5 is titled: On location!
Keywords: Cost accounting